Наземное лазерное сканирование прожекторной мачты; Известия вузов. Физика; Т. 57, № 9/3 - Токмаков Е. В. Евгений Владимирович; Павлов О. В. Олег Владимирович; Манабаев К. К. Кайрат Камитович; Павлов М. С. Михаил Сергеевич; Яковлев А. Н. Алексей Николаевич (2014, 2014)
Заглавие с экрана